2012
DOI: 10.1007/s11481-012-9363-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Curcuminoids Against Inflammation-Mediated Dopaminergic Neurodegeneration in the MPTP Model of Parkinson’s Disease

Abstract: The present study investigated the neuroprotective effect of curcuminoids, the active polyphenols of Curcuma longa (L.) rhizomes against inflammation-mediated dopaminergic neurodegeneration in the 1-methyl-4-phenyl-1,2,3,6- tetrahydropyridine (MPTP) model of Parkinson's disease (PD). Male C57BL/6 mice were pre-treated with curcuminoids (150 mg/kg/day) for 1 week, followed by four intra-peritoneal (i.p.) injections of MPTP (20 mg/kg) at 2 h intervals with further administration of curcuminoids or deprenyl (3 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…Chalcones (synthetic or natural) with capacity to reduce NO or attenuate iNOS expression are known to prevent neurological injury in experimental models (Li et al ., 2012; Ojha et al ., 2012) and could reduce otherwise elevated levels of neurotoxic molecules including peroxynitrite ONOO(−) directly responsible for invoking neurotoxicity (Kouti et al ., 2013). The capacity of specific flavonoids to reduce both NO and superoxide can lessen nitrosative stress-induced protein aggregates and prevent formation of peroxynitrite (Chen et al ., 2012; Drechsel et al ., 2012; Mandawad et al ., 2013) which initiates faulty autophagy, a failure of required degradative processes and greater likelihood of accumulated neurotoxic aggregate-prone proteins (i.e., alpha-synuclein) (Sarkar et al ., 2011; Liu et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Chalcones (synthetic or natural) with capacity to reduce NO or attenuate iNOS expression are known to prevent neurological injury in experimental models (Li et al ., 2012; Ojha et al ., 2012) and could reduce otherwise elevated levels of neurotoxic molecules including peroxynitrite ONOO(−) directly responsible for invoking neurotoxicity (Kouti et al ., 2013). The capacity of specific flavonoids to reduce both NO and superoxide can lessen nitrosative stress-induced protein aggregates and prevent formation of peroxynitrite (Chen et al ., 2012; Drechsel et al ., 2012; Mandawad et al ., 2013) which initiates faulty autophagy, a failure of required degradative processes and greater likelihood of accumulated neurotoxic aggregate-prone proteins (i.e., alpha-synuclein) (Sarkar et al ., 2011; Liu et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Rats treated with curcumin were relatively resistant to 3NP-induced striatal damage and exhibited preservation of mitochondrial function compared with vehicle-treated rats exposed to 3NP (Sandhir et al, 2014) 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) was originally identified as a contaminant of heroin that was responsible for the rapid development of PD-like symptoms in several young drug users. MPTP causes a highly selective degeneration of dopaminergic neurons in the substantia nigra of mice and monkeys and has therefore been widely used to model PD in these animals (Duan and Mattson, 1999;Maswood et al, 2004) Treatment of mice with curcumin protected dopaminergic neurons against MPTP-induced degeneration by a mechanism involving reduced inflammation (Ojha et al, 2012). Sulforaphane administration also protected mice against MPTP-induced degeneration of substantia nigra dopaminergic neurons, and suppressed gliosis and inflammation (Jazwa et al, 2011).…”
Section: B Environmental Toxicantsmentioning
confidence: 99%
“…Mice were divided into the following groups: Behavioral analysis: rota-rod task We created a mouse PD model and assessed it on a rota-rod apparatus (Panlab, LE8500) following a previously described procedure. 71,72 The instrument has a 30-mm diameter rotating rod and was divided into 5 compartments, thus permitting tests for 5 mice at a time. The rotation speed of the rod was fixed at 12 rpm and mice were tested for the total duration of 180 sec.…”
Section: Establishment Of a Chronic Pd Model In Monkeysmentioning
confidence: 99%